Application of S-UTD-CH Model into Multiple Diffraction Scenarios - Mehmet Baris Tabakcioglu; Ahmet Cansiz (International Journal of Antennas and Propagation)
Propagation prediction models based on ray tracing in coverage estimation for digital broadcasting systems are compared. Geometrical Theory of Diffraction (GTD), Slope Uniform Theory of Diffraction (S-UTD), and Slope UTD with Convex Hull (S-UTD-CH) models are compared for computation time and propagation path loss. S-UTD-CH model is optimum model with respect to computation time and relative path loss.